Effect of laser textured DLC coated AISI 52100 steel on the tribological behavior for engine applications / Arslan Ahmed - Arslan, Ahmed (2017)
The demand of high efficiency from automotive sector has become increasingly higher in the last few decades because of global attention towards environmental destruction, fuel economy and depletion of resources. Some of the approaches adopted to improve efficiency comprise of component's weight reduction, increase in running temperature of engine and the use of Diamond-like Carbon (DLC) coatings. The demand for higher performance from industries has pushed DLC coatings performance to their limit. Alternative methods have to be devised to further improvement their properties. Laser surface texturing can be one of the most promising techniques for improving performance of DLC coatings. The tribological performance of laser surface texturing in steel/steel contact has been found to be dependent on the texture density, diameter and depth. The first part of this thesis evaluates the possibility of improvement in amorphous hydrogenated carbon (a-C:H) coating performance through indirect laser texturing; and also, the effect of variation in texture densities, diameters and depths under the boundary lubricated conditions. Texture density, diameter and depth were varied from 10-30 %, 50-150 μm and 6-30 μm, respectively. The second, third and fourth parts of this thesis evaluate the tribological performance of laser textured amorphous hydrogenated carbon (a-C:H) and tetrahedral amorphous carbon (ta-C) coatings under various temperatures (40 to 125 ºC). To date, most of the automotive lubricants are mineral oil based, which is toxic and non-biodegradable. Because of this reason, vegetable oils are being explored as alternative base oils. In this thesis, tribological behavior of palm oil based trimethylolpropane (TMP) ester was evaluated as an alternative to the conventional base oil with textured and un-textured DLC’s. Comparison was conducted between textured/un-textured coatings at various temperatures in the presence of polyalphaolefin (PAO) and TMP ester lubricants. Coating hardness and Elastic modulus were investigated using nano-indentation. Adhesion of coating was analyzed using Rockwell-C indentation test. The tribological testing was conducted using the ball on plate reciprocating test rig. After the tribological testing, wear track topology was analyzed using a scanning electron microscope (SEM) and an atomic force microscope (AFM). The chemical composition of the worn surface was investigated using an energy dispersive spectroscopy (EDX). Structural changes of DLC coatings were investigated using a micro raman spectroscopy. The results indicated that the optimum texture density, diameter and depth of 20 %, 100 μm and 6 μm respectively could enhance the tribological performance of textured amorphous hydrogenated carbon coating. Laser textured a-C:H and ta-C coatings showed a lower wear coefficient at all temperatures tested; however, coefficient of friction is higher at 80 ºC and 125 ºC. This can be related to the lower graphitization in the case of textured coatings. Textured and un-textured ta-C coating showed lower friction and wear compared to textured and un-textured a-C:H coating. The results also indicated that micro textured DLC’s show a stable coefficient of friction with TMP ester even at 125 ºC.